The Effect of Motivational and Educational Self-Talk on the Dart Throwing Performance with Different Difficulties - Pouya Biabani; Amir Dana (University of Tehran, 2022)
The aim of the present study was to investigate the effect of educational and motivational self-talk on dart throwing performance with different difficulties. A total of 60 beginners and right-handers with an age range of 22 to 28 years were randomly selected and randomly divided into three groups of educational self-talk, motivation and control. The study groups performed 5 groups of 12 attempts according to their instructions. All throws were performed at low difficulty level at a distance of 1.80 m, at medium difficulty level at a distance of 2.37 m and at high difficulty level at a distance of 2.87 m from the dartboard. The performance measurement index was evaluated based on the amount of radial error (distance of the dart from the center). The statistical method of two factor analysis of variance analysis was used with repeated measurements in the difficulty level factor for testing hypotheses. The results showed that educational and motivational self-talk led to significant improvement in the dart throw performance. Also, the effect of difficulty was significant, and finally, the interactive effect of self-talk and difficulty on the performance of the dart throwing was significant. In simple tasks, due to the nature of the skill, educational self-talk based on related cues seems to improve the skill well, but at a moderate difficulty level, the role of motivational self-talk seems to become more prominent because the situation requires more effort for success, and this is consistent with the relationship between task difficulty and performance.